2021
DOI: 10.1007/978-3-030-67498-4_1
|View full text |Cite
|
Sign up to set email alerts
|

Between Origin and Destination: German Migrants and the Individual Consequences of Their Global Lives

Abstract: During the twentieth century, international migration was mainly understood as immigration into economically highly developed welfare states. This has changed over the course of recent decades because these countries are meanwhile also understood as important sources of international mobility. Whereas international mobility experiences have potentially far-reaching consequences for social inequalities and life chances, migration studies have only little experience in analysing international migration from thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…In their previously referenced study on emigrants from China to the United States, Liang and Morooka (2004) showed that approximately one‐third of the emigrant population were college graduates; more than 40% of the non‐emigrant population had only an elementary‐level education. A few other studies have identified a similar trend in which people with higher education levels are more likely to gravitate towards emigration (Atoyan et al, 2016; Canache et al, 2013; Erlinghagen et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 71%
See 1 more Smart Citation
“…In their previously referenced study on emigrants from China to the United States, Liang and Morooka (2004) showed that approximately one‐third of the emigrant population were college graduates; more than 40% of the non‐emigrant population had only an elementary‐level education. A few other studies have identified a similar trend in which people with higher education levels are more likely to gravitate towards emigration (Atoyan et al, 2016; Canache et al, 2013; Erlinghagen et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 71%
“…Previous studies have investigated the demographic patterns and socioeconomic selectivity of emigrants, commonly adopting demographic factors, including age, education, income, gender, marital status and occupation, to identify emigrants’ specific demographic patterns (Findley, 1987; Massey et al, 1994). These studies have usually found that the typical emigrant is young, well‐educated, unmarried and male (Desai et al, 2001; Erlinghagen et al, 2021; Liang & Morooka, 2004). However, variations in the demographic patterns of emigrants have also been found, particularly when emigration is driven by various factors simultaneously (Ailenei et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One of the gaps in migrant health research is low prioritisation of global health and public health training, unlike in the UK and the USA, where global health education is well established 76 77. Another methodological challenge identified by the German Emigration and Remigration Panel Study) for high-quality migrant health research constitutes the lack of detailed information on nationality, duration of stay and socioeconomic status in national registries, therefore, limiting reflections on diversity and heterogeneity in the German population 78. These factors may contribute to the observed lack of precision with regard to the effect estimates and generalisation of most of our findings 79.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses are based primarily on the German Emigration and Remigration Panel Study (GERPS), which provides information on internationally mobile Germans (Erlinghagen et al, 2021). GERPS assembles longitudinal data on both German emigrants and remigrants to assess the consequences of migration in the life course.…”
Section: Methodsmentioning
confidence: 99%